Analysis of the most influential Spanish digital newspapers and their presence on social networks - Zamarra López, Mª Mercedes (Estudios sobre el Mensaje Periodístico, 2015)
Social networks have radically change the media landscape and have become tools of human and social communication with a great relevance in today’s society. Enterprises, humans and the media uses them aiming to influence a greater number of people, from anywhere in the world and any time. The large media have had to adapt to this new journalism 2.0 and the users themselves have taken on the role of transmitters of information in real time. Therefore, this piece of work aims to study the relationship between the four spanish media major and social networks, as well as the effective interaction provided by its journalists.